Composition and bactericidal activity against beneficial and pathogenic bacteria of oregano essential oils from four chemotypes of origanum and lippia genus (2012)
Several studies have showed the antibacterial activity of oregano essential oils (OEO) chemotypes, carvarol and thymol against Gram positive and Gram negative pathogenic bacteria, but lack information on OEO antibacterial activity against beneficial bacteria. The object of this study was to compare the composition and minimum bactericidal concentration (MBC) of Origanum gender chemotypes: O. vulgare L. ssp. hirtum (OH), O. majorana (OM) y O. vulgare L. (OL) harvested in Colombia, against Lippia origanoides Kunth (LO) from Alto Patía in Colombia, and O. vulgare L. ssp. hirtum (OG) from Greece. The OEO composition was analyzed by gas chromatography coupled to mass spectrometer and its antibacterial activity by broth dilution and agar culture method. Three chemotypes were evaluated, OH and OG were carvacrol-type, LO and OL were thymol-tipe and OM was rich in sabinyl compound. The highest precursors content was showed to OEO from oregano varieties produced under greenhouse conditions at high altitude. The same bactericidal activity against Salmonella enteritidis (0.098 mg/mL) for OH and LO was founded. The lowest bactericidal activity against beneficial bacteria Lactobacillus acidophilus and Bifidobacterium breve was observed for OM (6.25 mg/mL) and LO (50 mg/mL), respectively. These results showed that LO native to Colombia had a comparable effect to OH and carvacrol against pathogenic enterobacteria and the lowest bactericidal activity against beneficial bacteria. These results showed a selective bactericidal effect against pathogenic beneficial bacteria of Origanum ssp. and L. origanoides chemotypes. A good potential to use L. origanoides as antimicrobial additive for animal and human health was found.